Porous lithium metatitanate type lithium ion sieve and preparation method thereof

Through suspension granulation method and surface hydrophobic modification treatment, porous lithium titanate type lithium ion sieve with high mechanical strength and stable adsorption capacity was prepared, which solved the high dissolution and circulation of existing lithium ion sieve in industrial applications. The problem of poor stability has achieved simplification of the process and industrial application.

CN119114005APending Publication Date: 2024-12-13CENT SOUTH UNIV

Patent Information

Application Number
CN202411268085.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing lithium-ion sieves have problems such as high dissolution loss, difficulty in filtration, and poor circulation stability in industrial applications, and the molding method is difficult to operate, which is not conducive to industrial promotion.

Method used

The porous lithium titanate type lithium ion sieve is formed by suspended granulation method, and the lithium titanate powder is synthesized by solid phase method, and the surface hydrophobic modification is performed, combining the aqueous phase of gelatin and dispersant with styrene and diethyl The oil phase of ethylene benzene is suspended and polymerized to form a porous structure with high mechanical strength, uniform particle size distribution and stable structure.

Benefits of technology

It improves the mechanical strength, particle size distribution uniformity, recycling effect and adsorption capacity stability of lithium ion sieve, simplifies the production process, reduces the difficulty of operation, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114005A_ABST
    Figure CN119114005A_ABST
Patent Text Reader

Abstract

The invention discloses a porous lithium metatitanate type lithium ion sieve and a preparation method thereof, and belongs to the technical field of new materials. The preparation method comprises the following steps: synthesizing lithium metatitanate powder by taking titanium dioxide and lithium carbonate as raw materials through a solid-phase method; carrying out surface hydrophobic modification treatment on the lithium metatitanate powder by adopting a silane coupling agent to obtain modified lithium metatitanate powder; the preparation method comprises the following steps: by taking a water solution containing gelatin and a dispersing agent as a water phase and a mixed solution containing a styrene monomer, a divinylbenzene cross-linking agent, an initiator and a pore-forming agent as an oil phase, carrying out suspension polymerization to obtain composite particles; the composite particles are firstly eluted to remove the pore-forming agent, and then are subjected to acidification transformation, so that the lithium ion sieve with high mechanical strength, uniform particle size distribution, stable structure, good recycling effect and stable adsorption capacity is obtained, the use capability of the lithium ion sieve in the industrial application process is effectively improved, and the service life of the lithium ion sieve is prolonged. The technical problems that a powdery lithium ion sieve is high in solution loss, difficult to filter and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium ion sieve, in particular to a porous lithium metatitanate type lithium ion sieve, and also to a preparation method of the porous lithium metatitanate type lithium ion sieve, belonging to the technical field of new materials. Background Art

[0002] In recent years, with the application and development of new energy technologies, the demand for lithium as a new energy metal has gradually increased. Lithium-containing materials are widely used in aerospace, energy, glass, batteries and other fields. Among them, lithium is particularly widely used in the field of batteries. Compared with traditional batteries, lithium-ion batteries have characteristics such as high specific energy, long service life, and high power. At this stage, they have been widely used in related industries such as automobile production and electrical appliance manufacturing.

[0003] A large amount of data shows that there are a large amount of liquid lithium resources in salt lake brine, underground brine and seawater, and the content is much higher than that of ore lithium resources. However, due to the simultaneous presence of multiple ions in the water body and the low content of lithium ions, it is difficult to separate and purify lithium resources. Studies have shown that the lithium ion sieve adsorption method has great application advantages for the extraction of low-grade, high magnesium-lithium ratio liquid lithium resources. Lithium metatitanate (Li2TiO3) is an excellent lithium ion sieve, but the powdered lithium ion sieve will have problems such as high dissolution loss, difficulty in filtering, and poor fluidity during actual application. Molding lithium metatitanate powder to prepare a lithium ion sieve with a certain mechanical and void structure can effectively solve this problem, thereby promoting the industrial application of lithium metatitanate lithium ion sieves. Chinese patent CN109621922A discloses an integral phenolic resin-based lithium ion sieve, which uses a mesoporous phenolic resin as a carrier, and lithium metatitanate particles are distributed in its pores. While solving the problems of the difficulty of separation and operation of the powdered lithium ion sieve after adsorption, it also takes into account the lithium ion sieve Li + The high-efficiency adsorption and separation capability of the lithium ion sieve is high. However, the operation difficulty of the molding method of the lithium ion sieve is large, which is not conducive to the promotion of industrial production. In addition, the integral phenolic resin / HMn2O4 lithium ion sieve exhibits excellent adsorption performance, with a maximum adsorption capacity of up to 30.1 mg / g, but its cycle stability is relatively poor. After 6 cycles of regeneration, the adsorption capacity can only be maintained at 90% of the initial adsorption capacity. Summary of the invention

[0004] In view of the technical defects existing in the prior art, the first object of the present invention is to provide a porous lithium titanate lithium ion sieve, which has the advantages of high mechanical strength, uniform particle size distribution, stable structure, good recycling effect, stable adsorption capacity, etc., which effectively improves the use ability of the lithium ion sieve in the industrial application process and solves the technical problems of high dissolution loss and difficult filtration of powdered lithium ion sieve.

[0005] The second object of the present invention is to provide a method for preparing a porous lithium titanate type lithium ion sieve, which utilizes a suspended granulation method for molding, and has the advantages of stable molding effect, high production efficiency, simple process, etc. At the same time, the method performs surface hydrophobic modification pretreatment on the lithium titanate powder, which can solve the shortcomings of lithium titanate having good hydrophilicity, uneven distribution, and low powder utilization rate during the organic polymerization process.

[0006] In order to achieve the above technical objectives, the present invention provides a method for preparing a porous lithium metatitanate type lithium ion sieve, which comprises the following steps:

[0007] 1) Using titanium dioxide and lithium carbonate as raw materials, lithium metatitanate powder is synthesized by a solid phase method;

[0008] 2) subjecting the lithium metatitanate powder to surface hydrophobic modification using a silane coupling agent to obtain modified lithium metatitanate powder;

[0009] 3) using an aqueous solution containing gelatin and a dispersant as an aqueous phase, and a mixed solution containing a styrene monomer, a divinylbenzene crosslinking agent, an initiator and a pore-forming agent as an oil phase, adding the oil phase and the modified lithium metatitanate powder into the aqueous phase, and performing suspension polymerization to obtain composite particles;

[0010] 4) The composite particles are firstly washed to remove the pore-forming agent, and then acidified to obtain a porous lithium metatitanate type lithium ion sieve.

[0011] The preparation method of the porous lithium metatitanate type lithium ion sieve provided by the present invention, first, the solid phase method is used to synthesize lithium metatitanate to ensure the purity of lithium metatitanate, and based on the hydrophilicity of lithium metatitanate itself, it is difficult to be evenly dispersed in the hydrophobic polymer, the present invention adopts the surface hydrophobic modification method of lithium metatitanate, and the surface of lithium metatitanate is modified by a silane coupling agent to enhance its hydrophobicity, thereby ensuring that lithium metatitanate can be stably dispersed in the oil phase during the suspension polymerization molding process, and then can be further effectively distributed inside and on the surface of the polymerized particles. Secondly, styrene and divinylbenzene are used to construct a porous resin by polymerization and cross-linking, and the formed resin particles have the characteristics of developed pore structure, high mechanical strength, good stability, etc., and lithium metatitanate powder is loaded with it as a carrier, which can improve the stability of the material, and can fully expose the adsorption sites of lithium metatitanate, and improve the adsorption activity. Thirdly, suspension polymerization is used to realize granulation, and particles with uniform particle size distribution and high sphericity can be obtained, and a pore-forming agent is introduced in the granulation process to improve the porosity of the granular material. In summary, the porous lithium metatitanate type lithium ion sieve prepared by the present invention has the advantages of high mechanical strength, uniform particle size distribution, stable structure, good recycling effect, stable adsorption capacity, etc.

[0012] As a preferred solution, the process of synthesizing lithium metatitanate powder by the solid phase method is: titanium dioxide and lithium carbonate are uniformly mixed and then calcined, and the calcined product is ground to obtain lithium metatitanate powder.

[0013] As a more preferred solution, the calcination condition is: calcination at a temperature of 750-850° C. for 12-24 hours. Under the preferred calcination temperature and calcination time, the reaction energy consumption can be reduced while ensuring that lithium carbonate and titanium dioxide are fully converted into lithium metatitanate.

[0014] As a more preferred solution, the molar ratio of lithium carbonate to titanium dioxide is 1.01 to 1.05. By optimizing the ratio of lithium carbonate and titanium dioxide to an appropriate range, the two raw materials can be fully reacted and the residual amount of the reactants can be reduced.

[0015] As a preferred solution, the process of using a silane coupling agent to perform surface hydrophobic modification on the lithium metatitanate powder is as follows: the lithium metatitanate powder is dispersed in water under the action of a dispersant, and then a silane coupling agent is added for hydrolysis. The lithium metatitanate powder is surface modified with a silane coupling agent to enhance its hydrophobicity, thereby ensuring that the lithium metatitanate powder can be stably dispersed in the oil phase during the suspension polymerization process, and then it can be effectively distributed inside and on the surface of the spherical particles during the polymerization of styrene and divinylbenzene, thereby ensuring the uniformity of the distribution of the lithium metatitanate particles in the synthesized spherical particles.

[0016] As a more preferred solution, the concentration of the dispersant in water is 1 to 3 g / L.

[0017] As a more preferred solution, the dispersant includes sodium dodecylbenzene sulfonate. Selecting sodium dodecylbenzene sulfonate as the dispersant and controlling its addition amount can promote the full dispersion of lithium metatitanate powder in water, thereby facilitating the modification treatment of the lithium metatitanate powder by the silane coupling agent.

[0018] As a more preferred solution, the silane coupling agent includes at least one of KH570, KH550 and octyltrimethoxysilane. The preferred silane coupling agent contains a long-chain alkyl hydrophobic group, and the hydrophobic group is modified on the surface of the lithium metatitanate powder mainly by hydrolysis.

[0019] As a preferred solution, the mass of the silane coupling agent is 1-5% of the mass of the lithium titanate powder. If the amount of the silane coupling agent is too low, the purpose of hydrophobic modification of the lithium titanate powder cannot be achieved. If the amount of the silane coupling agent is too high, excessive hydrophobic groups will be wrapped on the surface of the lithium titanate powder, which will reduce the adsorption activity.

[0020] As a more preferred solution, the concentration of gelatin in the aqueous phase is 1-10 g / L, and the concentration of the dispersant is 0.5-5 g / L. The introduction of gelatin can improve the sphericity of the composite particle material. The dispersant is conducive to the emulsification and dispersion of the organic phase to form uniform oil droplets.

[0021] As a more preferred solution, the mass ratio of styrene, divinylbenzene and pore-forming agent in the oil phase is 15-25:15-25:35-45, and the mass of the initiator is 1-5% of the total mass of styrene and divinylbenzene; styrene is used as a polymerization monomer, and divinylbenzene is used as a cross-linkable polymerization monomer, and the ratio of the two affects the cross-linking degree of the resin, thereby affecting the porosity. For example, if the styrene monomer content ratio is too high, its cross-linking degree is reduced, and it is difficult to form a large number of micro-mesoporous structures. If the styrene ratio is too low, its cross-linking degree is too high, and it is easy to produce cross-linked dense areas. The content of the pore-forming agent also affects the porosity of the resin. If its content is too low, the porosity will be too low, and if its content is too high, it will affect the mechanical strength of the resin.

[0022] As a more preferred solution, the volume ratio of the water phase to the oil phase is 1 to 10:10.

[0023] As a more preferred solution, the dispersant includes polyvinyl alcohol.

[0024] As a preferred solution, the pore-forming agent includes at least one of toluene, solid paraffin, liquid paraffin, n-heptane, hexane, and octane. The pore structures of lithium ion sieves prepared by different pore-forming agents are different, which affects their specific surface area and mechanical strength, so the appropriate pore-forming agent is selected according to the needs.

[0025] As a preferred embodiment, the initiator includes benzoyl peroxide.

[0026] As a preferred solution, the suspension polymerization includes a granulation reaction stage and a hardening reaction stage: the conditions of the granulation reaction stage are: temperature of 75-83°C, time of 2-3 hours, stirring speed of 200-400rpm; the conditions of the hardening reaction stage are: temperature of 85-95°C, time of 1-2 hours. The control of the stirring rate during the suspension polymerization process is very important. Too low a stirring rate will cause the lithium titanate powder to be deposited at the lower end of the reactor, resulting in insufficient reaction. A higher stirring rate will result in a finer particle size and poor sphericity of the polymerized particles. In addition, the temperature environment in the granulation reaction stage is maintained at 75-83°C. Under this temperature condition, the polymerization reaction can be ensured to proceed slowly and evenly, and the granulation process is stable. The temperature environment in the hardening reaction stage is relatively high, mainly to further rapidly polymerize and cross-link the remaining part of the polymerized monomers in the particles, thereby rapidly hardening to effectively improve the mechanical strength.

[0027] As a preferred solution, the process of removing the pore-forming agent by elution is: soaking in ethanol, the liquid-to-solid mass ratio of soaking is 10-20:1, and the soaking time is 9-12 hours. Under the preferred conditions, the pore-forming agent can be fully dissolved.

[0028] As a preferred solution, the acidification transformation process is: soaking in 0.1-0.5 mol / L hydrochloric acid for 8-12 hours. Using hydrochloric acid as a transformation agent to elute lithium ions, under the optimized acidification transformation conditions, the lithium ion sieve can be fully transformed while reducing the dissolution loss of titanium in the lithium ion sieve to ensure the structure of the lithium ion sieve.

[0029] The present invention also provides a porous lithium metatitanate type lithium ion sieve, which is obtained by the preparation method. The porous lithium metatitanate type lithium ion sieve of the present invention has the advantages of high mechanical strength, uniform particle size distribution, stable structure, good recycling effect, stable adsorption capacity, etc.

[0030] Compared with the existing lithium ion screen forming technology, the technology proposed by the present invention has the following advantages:

[0031] 1) The porous lithium metatitanate lithium ion sieve provided by the present invention has the advantages of high mechanical strength, uniform particle size distribution, stable structure, good recycling effect, stable adsorption capacity, etc.

[0032] 2) The present invention adopts a suspension granulation molding process, which has the advantages of stable molding effect, high production efficiency, simple process, etc., and is conducive to large-scale industrial application.

[0033] 3) In the process of preparing the porous lithium titanate type lithium ion sieve, the present invention performs surface hydrophobic modification on the lithium titanate powder to enhance its hydrophobicity, thereby ensuring that the lithium titanate powder can be formed by suspension granulation and can achieve uniform distribution of the lithium titanate in the polypropylene resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a process flow chart for preparing porous lithium titanate type lithium ion sieve.

[0035] Figure 2 This is the XRD characterization of the samples in Examples 1 to 5.

[0036] Figure 3 This is the contact angle measurement of the modified lithium titanate powder of Example 2.

[0037] Figure 4 SEM characterization of the lithium ion sieve prepared in Example 3.

[0038] Figure 5 SEM characterization of the lithium ion sieve prepared in Example 4.

[0039] Figure 6 SEM characterization of the lithium ion sieve prepared in Example 5.

[0040] Figure 7 The specific surface area test results of the lithium ion sieves prepared in Examples 3, 4 and 5.

[0041] Figure 8 The cyclic adsorption capacity of the lithium ion sieves prepared in Examples 4 and 5.

[0042] Fig. 9 Comparison of samples of Example 5 and Example 6. DETAILED DESCRIPTION

[0043] In order to better illustrate the embodiments of the present invention, the specific embodiments in the examples of the present invention will be clearly and completely described below. The examples are only used to explain the content of the present invention and do not constitute any limitation on the scope of protection of the claims of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the manufacturer's recommended conditions are used. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0044] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0045] Example 1

[0046] This embodiment provides a method for preparing lithium metatitanate powder, which specifically comprises the following steps:

[0047] Step 1: Accurately weigh a certain amount of lithium carbonate and titanium dioxide in a beaker, and control the molar ratio of the two substances to be 1.05:1.

[0048] Step 2: Use alcohol to mix the two substances thoroughly, put the mixed sample into an oven, and dry it at 100°C for 30 minutes.

[0049] Step 3: Transfer the dried sample to a corundum crucible, and then transfer it to an electric furnace. Set the heating rate of the electric furnace to 5°C / min and heat it to 750°C, then keep it warm and calcine it for 12 hours.

[0050] Step 4: Grind the calcined sample to obtain powdered lithium metatitanate.

[0051] Example 2

[0052] This embodiment provides a silane modification method for lithium metatitanate, which specifically includes the following steps:

[0053] Step 1: Accurately weigh 20 g of powdered lithium metatitanate and dissolve it in 200 ml of sodium dodecylbenzene sulfonate solution with a mass concentration of 1.0 g / L.

[0054] Step 2: Accurately transfer 0.5 ml of octyltrimethoxysilane coupling agent to the mixed solution and stir the mixture at 45°C for 1 hour.

[0055] Step 3: Filter the mixed solution after the reaction is completed, rinse with alcohol, place the filter cake in an oven, and dry it at 120°C for 2 hours.

[0056] Example 3

[0057] This embodiment provides a method for preparing a lithium metatitanate type lithium ion sieve, which specifically comprises the following steps:

[0058] Step 1: Mix 125 ml of a gelatin aqueous solution with a mass concentration of 14 g / L, 125 ml of a polyvinyl alcohol solution with a mass concentration of 7 g / L, and 250 ml of a pure water solution as the aqueous phase.

[0059] Step 2: Mix 25 ml of styrene, 25 ml of divinylbenzene and 1.5 g of initiator benzoyl peroxide evenly as the oil phase.

[0060] Step 3: Slowly transfer the water phase, oil phase and 20 g of modified powder into a separate reactor, keeping the stirring blade speed at 300 rpm.

[0061] Step 4: After mixing evenly, use a water bath to slowly heat the system to 83°C and keep it stable, enter the suspension granulation stage, and maintain the reaction system unchanged for 3 hours. After the suspension granulation stage, slowly continue to heat the system to 95°C, keep the stirring blade speed unchanged, enter the particle hardening stage, and maintain the reaction system unchanged for 1 hour.

[0062] Step 5: After the reaction is completed, accurately weigh 5 g of the sieved and washed granulated lithium ion sieve precursor and transfer it to an adsorption column. Cycle the column in 200 ml of 0.5 mol / L hydrochloric acid for 8 hours to obtain a titanium-based lithium ion sieve.

[0063] Example 4

[0064] This embodiment provides a method for preparing a porous lithium metatitanate lithium ion sieve, which specifically comprises the following steps:

[0065] Step 1: Mix 125 ml of a gelatin aqueous solution with a mass concentration of 14 g / L, 125 ml of a polyvinyl alcohol solution with a mass concentration of 7 g / L, and 250 ml of a pure water solution as the aqueous phase.

[0066] Step 2: Mix 25 ml of styrene, 25 ml of divinylbenzene, 75 ml of toluene and 1.5 g of initiator benzoyl peroxide evenly as the oil phase.

[0067] Step 3: Slowly transfer the water phase, oil phase and 20 g of modified powder into a separate reactor, keeping the stirring blade speed at 300 rpm.

[0068] Step 4: After mixing evenly, use a water bath to slowly heat the system to 83°C and keep it stable, enter the suspension granulation stage, and maintain the reaction system unchanged for 3 hours. After the suspension granulation stage, slowly continue to heat the system to 95°C, keep the stirring blade speed unchanged, enter the particle hardening stage, and maintain the reaction system unchanged for 1 hour.

[0069] Step 5: After the reaction is completed, the screened and washed lithium ion sieve precursor is transferred to a Soxhlet extractor containing 200 ml of ethanol solution and extracted at 95° C. for 9 hours.

[0070] Step 5: After the reaction is completed, accurately weigh 5 g of the sieved and washed granulated lithium ion sieve precursor and transfer it to an adsorption column. Cycle transformation is performed under the action of 200 ml, 0.5 mol / L hydrochloric acid for 8 hours to obtain a porous titanium-based lithium ion sieve.

[0071] Example 5

[0072] This embodiment provides a method for preparing a porous lithium metatitanate lithium ion sieve, which specifically comprises the following steps:

[0073] Step 1: Mix 125 ml of a gelatin aqueous solution with a mass concentration of 14 g / L, 125 ml of a polyvinyl alcohol solution with a mass concentration of 7 g / L, and 250 ml of a pure water solution as the aqueous phase.

[0074] Step 2: Mix 25 ml of styrene, 25 ml of divinylbenzene, 75 ml of n-heptane and 1.5 g of initiator benzoyl peroxide evenly as the oil phase.

[0075] Step 3: Slowly transfer the water phase, oil phase and 20 g of modified powder into a separate reactor, keeping the stirring blade speed at 300 rpm.

[0076] Step 4: After mixing evenly, use a water bath to slowly heat the system to 83°C and keep it stable, enter the suspension granulation stage, and maintain the reaction system unchanged for 3 hours. After the suspension granulation stage, slowly continue to heat the system to 95°C, keep the stirring blade speed unchanged, enter the particle hardening stage, and maintain the reaction system unchanged for 1 hour.

[0077] Step 5: After the reaction is completed, the screened and washed lithium ion sieve precursor is transferred to a Soxhlet extractor containing 200 ml of petroleum ether solution and extracted at 95° C. for 9 hours.

[0078] Step 6: After the reaction is completed, accurately weigh 5 g of the sieved and washed granulated lithium ion sieve precursor and transfer it to an adsorption column. Cycle transformation is performed under the action of 200 ml, 0.5 mol / L hydrochloric acid for 8 hours to obtain a porous titanium-based lithium ion sieve.

[0079] Example 6

[0080] This embodiment provides a method for preparing a porous lithium metatitanate lithium ion sieve, which specifically comprises the following steps:

[0081] Step 1: Mix 125 ml of a gelatin aqueous solution with a mass concentration of 14 g / L, 125 ml of a polyvinyl alcohol solution with a mass concentration of 7 g / L, and 250 ml of a pure water solution as the aqueous phase.

[0082] Step 2: Mix 25 ml of styrene, 25 ml of divinylbenzene, 75 ml of n-heptane and 1.5 g of initiator benzoyl peroxide evenly as the oil phase.

[0083] Step 3: Slowly transfer the water phase, oil phase and 20 g of modified powder into a separate reactor, keeping the stirring blade speed at 200 rpm.

[0084] Step 4: After mixing evenly, use a water bath to slowly heat the system to 83°C and keep it stable, enter the suspension granulation stage, and maintain the reaction system unchanged for 3 hours. After the suspension granulation stage, slowly continue to heat the system to 95°C, keep the stirring blade speed unchanged, enter the particle hardening stage, and maintain the reaction system unchanged for 1 hour.

[0085] Step 5: After the reaction is completed, the screened and washed lithium ion sieve precursor is transferred to a Soxhlet extractor containing 200 ml of petroleum ether solution and extracted at 95° C. for 9 hours.

[0086] Step 6: After the reaction is completed, accurately weigh 5 g of the sieved and washed granulated lithium ion sieve precursor and transfer it to an adsorption column. Cycle transformation is performed under the action of 200 ml, 0.5 mol / L hydrochloric acid for 8 hours to obtain a porous titanium-based lithium ion sieve.

[0087] The first embodiment describes the preparation method of powdered lithium metatitanate; the second embodiment describes the modification method of powdered lithium metatitanate; the difference between the third embodiment, the fourth embodiment and the fifth embodiment is that the third embodiment does not add any pore-forming agent, the pore-forming agent added in the fourth embodiment is toluene, and the pore-forming agent added in the fifth embodiment is n-heptane. The difference between the sixth embodiment and the fifth embodiment is the stirring rate of the reaction process, wherein the stirring rate of the sixth embodiment is 200 rpm.

[0088] The samples synthesized in Examples 1 to 5 were characterized by an X-ray diffractometer (Empyrean 2). The contact angle of the sample prepared in Example 2 was measured using water as the medium using a contact angle meter. The samples prepared in Examples 3 to 5 were characterized by a cold field emission electron microscope (JSM-7900F). The specific surface area of ​​the samples in Examples 3 to 5 was tested and analyzed using a fully automatic specific surface area analyzer (QUADRASORBevo). The mechanical strength of the samples in Examples 3 to 5 was tested using a mechanical strength tester. The cyclic adsorption performance of the samples in Examples 4 and 5 was tested using an inductively coupled plasma emission spectrometer (ICAP7400radial).

[0089] Figure 2 The XRD characterization of the samples of Examples 1 to 5 shows that the crystal form of lithium metatitanate obtained by calcining at 750°C for 12 hours is relatively complete and has obvious characteristic peaks. The characteristic peaks of lithium metatitanate modified by silane do not change, and the original crystal structure can be maintained. The characteristic peaks of the samples obtained by suspension granulation can also keep the crystal form of lithium metatitanate unchanged.

[0090] Figure 3 The results are shown for the contact angle measurement of lithium metatitanate modified with silane in Example 2 in water. The test results show that the lithium metatitanate modified under this condition has good hydrophobicity, and the contact angle reaches 141.72°.

[0091] Figure 4 , Figure 5 and Figure 6 They are SEM characterization pictures of granulation results under different conditions. Figure 4 This is the granulation result without adding pore-forming agent. Figure 5 The granulation results of adding toluene as a pore-forming agent. Figure 6 This is the granulation result with n-heptane added as pore-forming agent. Figure 4 It shows that the lithium ion sieve prepared without adding pore-forming agent has fewer holes, dense interior, and most of the lithium titanate powder is distributed on the outer surface of the particles. Figure 5 It shows that after adding some toluene as a pore-forming agent, an obvious void structure appears inside the particles, and lithium titanate powder is distributed on the inner pore surface and the outer surface of the particles. Figure 6 It is shown that after adding some n-heptane as a pore-forming agent, a larger pore structure appears inside the particles. Compared with toluene as a pore-forming agent, the pore diameter of the lithium ion sieve prepared with n-heptane as a pore-forming agent is larger.

[0092] Figure 7The specific surface area test data of the lithium ion sieve prepared in Examples 3 to 5 show that the specific surface area of ​​the lithium ion sieve without adding pore-forming agent in Example 3 is 2.517 m 2 / g, the specific surface area of ​​the lithium ion sieve in Example 4 with toluene added as a pore-forming agent is 261.140 m 2 / g, the specific surface area of ​​the lithium ion sieve in Example 5 with n-heptane added as a pore-forming agent is 65.310 m 2 / g. By adding pore-forming agent to the lithium ion sieve, the specific surface area of ​​the material is effectively increased, among which the lithium ion sieve prepared by adding toluene has the largest specific surface area.

[0093] Table 1 shows the mechanical strength test data of the lithium ion sieves prepared in Examples 3 to 5. Five lithium ion sieves in each example were randomly selected for testing. The test results showed that the average mechanical strength of the lithium ion sieve without adding a pore-forming agent was 5.74N, the average mechanical strength of the lithium ion sieve with toluene as a pore-forming agent was 4.41N, and the mechanical strength of the lithium ion sieve with n-heptane as a pore-forming agent was 5.02N. The mechanical strength of the lithium ion sieve decreased slightly after adding the pore-forming agent, which was caused by the porous structure of the particles.

[0094] Table 1 Mechanical strength distribution of lithium ion sieves prepared in Examples 3, 4 and 5 (unit: N)

[0095]

[0096] Figure 8 The figure shows the change in adsorption capacity of the porous lithium ion sieves prepared in Examples 4 and 5 during cyclic adsorption in a salt lake brine. The cyclic adsorption capacity of the porous lithium ion sieve prepared in Example 4 is stabilized at 4.11 mg / g, and the cyclic adsorption capacity of the sample prepared in Example 5 is stabilized at 3.88 mg / g. The adsorption capacity hardly decreases with continued cyclic use. Both lithium ion sieves can maintain stable adsorption capacity during multiple cyclic adsorption processes.

[0097] Fig. 9 Shown is a photo comparison of the samples prepared in Example 5 and Example 6. The difference in the preparation effects of the two materials lies in the particle size of the materials. The particle size of the material prepared at 300 rpm is generally distributed in the range of 0 to 1 mm, while the particle size of the sample prepared at 200 rpm is generally distributed in the range of 1 to 5 mm.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous lithium metatitanate type lithium ion sieve, characterized in that: The following steps are involved: 1) Using titanium dioxide and lithium carbonate as raw materials, lithium metatitanate powder is synthesized by a solid phase method; 2) subjecting the lithium metatitanate powder to surface hydrophobic modification using a silane coupling agent to obtain modified lithium metatitanate powder; 3) using an aqueous solution containing gelatin and a dispersant as an aqueous phase, and a mixed solution containing a styrene monomer, a divinylbenzene crosslinking agent, an initiator and a pore-forming agent as an oil phase, adding the oil phase and the modified lithium metatitanate powder into the aqueous phase, and performing suspension polymerization to obtain composite particles; 4) The composite particles are firstly washed to remove the pore-forming agent, and then acidified to obtain a porous lithium metatitanate type lithium ion sieve.

2. The method for preparing a porous lithium metatitanate lithium ion sieve according to claim 1, characterized in that: The process of synthesizing lithium metatitanate powder by the solid phase method is as follows: titanium dioxide and lithium carbonate are uniformly mixed and then calcined, and the obtained calcined product is ground to obtain lithium metatitanate powder.

3. The method for preparing a porous lithium metatitanate lithium ion sieve according to claim 2, characterized in that: The calcination conditions are: calcination at 750-850°C for 12-24 hours; The molar ratio of lithium carbonate to titanium dioxide is 1.01 to 1.

05.

4. The method for preparing a porous lithium metatitanate lithium ion sieve according to claim 1, characterized in that: The process of using a silane coupling agent to perform surface hydrophobic modification on the lithium metatitanate powder is as follows: the lithium metatitanate powder is dispersed in water under the action of a dispersant, and then the silane coupling agent is added for hydrolysis.

5. The method for preparing a porous lithium metatitanate lithium ion sieve according to claim 1, characterized in that: The concentration of the dispersant in water is 1 to 3 g / L; The dispersant includes sodium dodecylbenzene sulfonate; The silane coupling agent includes at least one of KH570, KH550 and octyltrimethoxysilane. The mass of the silane coupling agent is 1-5% of the mass of the lithium metatitanate powder.

6. The method for preparing a porous lithium metatitanate lithium ion sieve according to claim 1, characterized in that: The concentration of gelatin in the aqueous phase is 1-10 g / L, and the concentration of the dispersant is 0.5-5 g / L; The mass ratio of styrene, divinylbenzene and pore-forming agent in the oil phase is 15-25:15-25:35-45, and the mass of the initiator is 1-5% of the total mass of styrene and divinylbenzene; The volume ratio of the water phase to the oil phase is 1 to 10:

10.

7. The method for preparing a porous lithium metatitanate lithium ion sieve according to claim 6, characterized in that: The dispersant includes polyvinyl alcohol; The pore-forming agent includes at least one of toluene, solid paraffin, liquid paraffin, n-heptane, hexane and octane; and the initiator includes benzoyl peroxide.

8. The method for preparing a porous lithium metatitanate lithium ion sieve according to claim 1, characterized in that: The suspension polymerization includes a granulation reaction stage and a hardening reaction stage: the conditions of the granulation reaction stage are: temperature of 75-83°C, time of 2-3 hours, stirring speed of 200-400rpm; the conditions of the hardening reaction stage are: temperature of 85-95°C, time of 1-2 hours.

9. The method for preparing a porous lithium metatitanate lithium ion sieve according to claim 1, characterized in that: The process of removing the pore-forming agent by elution is as follows: soaking in ethanol, the liquid-to-solid mass ratio of the soaking is 10 to 20:1, and the soaking time is 9 to 12 hours; The acidification transformation process is: soaking in 0.1-0.5 mol / L hydrochloric acid for 8-12 hours.

10. A porous lithium metatitanate type lithium ion sieve, characterized in that: The method is obtained by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing spherical granular lithium ion sieve

    CN106084102A

  • Aluminum salt adsorbent and application thereof in extraction of lithium in salt lake brine

    CN108854996A

  • Titanium lithium ion sieve particle and preparation method thereof

    CN116809013A

Cited By

  • Lithium titanate coating diaphragm and preparation method thereof

    CN119864592A

  • Granular manganese lithium ion sieve and cross-linking granulation forming method thereof

    CN121607138A

  • Recycling method of lithium ion sieve adsorbent granulation mother liquor

    CN122516944A